Human Resources Practices and turnover intention in the pharmaceutical industry in China: A moderated mediation model - Yanhui, L.; Sousa, I.C.; Ramos, S. (XIII International Workshop on Human Resource Management, 2024)
The pharmaceutical industry in China faces difficulties in holding onto top talent, and there is a dearth of empirical research on the intention of employee turnover. Drawing on Social Exchange Theory, the relationship between human resources practices and turnover intention is examined in this study, with a focus on the mediating role of affective commitment and the moderating role of ownership. The results indicate that human resources practices have an indirect negative impact on turnover intention in the context of the Chinese pharmaceutical industry. Affective commitment fully mediates the relationship between human resources practices and turnover intention; and the relationship between human resources practices and turnover intention is impacted by different ownership. This research informs managers and employers in pharmaceutical companies on how to retain talent through the implementation of human resources practices that contribute to an emotional attachment from employees to the organization.